Effects of Visual and Lateral Line Organs on Reefing Behavior of Sebastes schlegelii - Feng CHEN; Jiao LI; Pihai GONG; Changtao GUAN (Progress in Fishery Sciences, 2025)
Artificial reefs are increasingly used in marine ecosystems to support biodiversity and provide refuge for fish species. To maximize the effectiveness of artificial reefs, understanding the mechanisms by which fish locate and aggregate around them is essential. Sensory cues are critical in guiding fish navigation and aggregation behaviors. Vision and the lateral line system are particularly important for detecting environmental features and predators among the primary sensory modalities. However, the specific contributions of these two sensory systems and their potential interactions in guiding fish toward artificial reefs remain poorly understood. This study investigated the effects of impairing the visual and lateral line systems, both independently and in combination, on the aggregation behavior of Sebastes schlegelii, a species that relies heavily on these sensory modalities for habitat selection.This study aimed to assess whether visual and lateral line system impairments affect the fish's ability to aggregate around artificial reefs. We designed six experimental groups to explore the impacts of various impairments on aggregation behavior. The groups were as follows: (1) Normal group with no sensory impairments; (2) Visual impairment group with visual cues blocked using physical methods to destroy; (3) Mild lateral line impairment group with the lateral line system partially disrupted using a gentle treatment; (4) Visual + mild lateral line impairment group with combined visual and mild lateral line impairments; (5) Severe lateral line impairment group, with the lateral line system extensively disrupted; and (6) Visual + severe lateral line impairment group, with severe impairments to both sensory systems. Aggregation behavior was measured by observing the number of fish within a defined proximity to an artificial reef over a 12-h period, which allowed us to examine immediate and sustained responses.Our findings demonstrated that fish in the normal group exhibited the highest levels of aggregation, confirming that visual and lateral line cues are essential for guiding fish towards artificial reefs. This supports the hypothesis that these sensory systems are crucial in habitat selection and aggregation. Fish in the visual and mild lateral line impairment groups showed significantly reduced aggregation compared with the normal group, suggesting that visual and lateral line cues are critical for efficient navigation and habitat selection. Notably, fish in the severe and visual + severe lateral line impairment groups exhibited even lower levels of aggregation, indicating that more severe impairments to either or both sensory systems result in further decreases in aggregation behavior.Notably, this study found no significant interaction between the two sensory impairments. Although impairing the visual and lateral line systems (either mildly or severely) resulted in a considerable reduction in aggregation compared to impairing either system alone, the effects were additive rather than synergistic. This means that impairing the two sensory systems did not result in a compounded or exaggerated loss of aggregation behavior. Instead, the loss of aggregation behavior owing to sensory impairments occurred independently for each system. For example, fish with only visual impairments showed reduced aggregation, and fish with only lateral line impairments showed a similar reduction. The combined impairments led to a further decrease in aggregation, which was not notably greater than the expected sum of the individual impairments.These results indicate that visual and lateral line systems are crucial for fish aggregation behavior; however, impairments to these systems do not synergistically amplify the overall effect. In particular, impairing both sensory systems reduces aggregation behavior more than impairing either system alone, but the lack of an interaction effect implies that the two systems do not jointly influence aggregation in a compounded manner. This finding has implications for understanding how fish navigate toward artificial reefs and could guide the design of future reef structures. For example, artificial reefs that target the enhancement of one sensory modality (such as visual cues) may remain effective in supporting fish aggregation, as the loss of one sensory system does not appear to severely compromise aggregation behavior.However, notably, these conclusions are based on the behavior of S. schlegelii in the context of this specific study. The lack of interaction between sensory systems in this species may not apply universally to all fish species. Some species may rely more heavily on one sensory modality over another, or they may exhibit different types of sensory integration. Therefore, further studies are needed to explore the sensory preferences and behavior of other fish species in relation to artificial reefs.This study also highlights the broader ecological implications of artificial reef design. Understanding the role of sensory systems in fish aggregation can inform strategies to optimize the placement and features of artificial reefs, making them more effective in supporting marine biodiversity. In particular, this study underscores the importance of considering the sensory ecology of target species when designing artificial habitats and provides valuable insights into how sensory impairments affect fish behavior and ecological interactions.